ANALISIS SISTEM INFORMASI AKUNTANSI ATAS PENGGAJIAN DAN PENGUPAHAN PADA PT. BATIK ARJUNA CEMERLANG SUKOHARJO - Christina Kurnia Agatha; Mulyadi Mulyadi (STIE AUB Surakarta, 2018)
The purpose of this study was to find out how the application of accounting information systems to payroll and wages at PT. Arjuna Cemerlang Sukoharjo Batik and to determine the effectiveness of the application of accounting information systems for payroll and wages in the company. The object of this research is in the company PT. Batik Arjuna Cemerlang in Sukoharjo, Central Java. This type of research is a type of descriptive research that uses primary data such as the results of interviews with companies and secondary parties such as observation, interviews, documentation methods, and library methods. The data analysis method used is descriptive method. This type of data in research uses qualitative data, namely data that cannot be measured in a numerical scale (numbers) or data that is presented in descriptive form or in the form of a description. The results of the research at PT. Arjuna Cemerlang Sukoharjo Batik concludes that the implementation of the accounting information system for payroll and wages has run according to the criteria required by PT. Batik Arjuna Cemerlang Sukoharjo. This proves from the results of the evaluation that the function officer associated with the employee salary payment procedure in the payroll system of PT. Arjuna Cemerlang Sukoharjo Batik has been done well, although there are still some shortcomings including the existence of double duty on the finance department,employee absenteeism and payroll records made by the company still using a manual system.Keywords: Accounting information system, Accounting information system of wages, Payroll and payment, Flowchart.